2017
DOI: 10.1016/j.jhydrol.2017.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Transport and fate of viruses in sediment and stormwater from a Managed Aquifer Recharge site

Abstract: a b s t r a c tEnteric viruses are one of the major concerns in water reclamation and reuse at Managed Aquifer Recharge (MAR) sites. In this study, the transport and fate of bacteriophages MS2, PRD1, and UX174 were studied in sediment and stormwater (SW) collected from a MAR site in Parafield, Australia. Column experiments were conducted using SW, stormwater in equilibrium with the aquifer sediment (EQ-SW), and two pore-water velocities (1 and 5 m day À1 ) to encompass expected behavior at the MAR site. The aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 115 publications
2
19
0
Order By: Relevance
“…Sasidharan et al (2017b) previously attributed this temperature dependency to slight increases in the adhesive interaction on heterogeneous surfaces and slight differences in mass transfer (η in Table 1). Similar to Sasidharan et al (2017a), it was found that k att1 > μ s1 >> μ l . Significantly, μ s1 was two and one orders of magnitude higher than μ l for PRD1, whereas μ s1 was two and three orders of magnitude higher than μ l for ΦX174 at 4 and 20°C, respectively.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Sasidharan et al (2017b) previously attributed this temperature dependency to slight increases in the adhesive interaction on heterogeneous surfaces and slight differences in mass transfer (η in Table 1). Similar to Sasidharan et al (2017a), it was found that k att1 > μ s1 >> μ l . Significantly, μ s1 was two and one orders of magnitude higher than μ l for PRD1, whereas μ s1 was two and three orders of magnitude higher than μ l for ΦX174 at 4 and 20°C, respectively.…”
Section: Resultssupporting
confidence: 60%
“…Phase III consisted of eluting the column with virus‐free 10 mM NaCl solution at a pore‐water velocity of 0.1 m d −1 . Columns were eluted with Milli‐Q water and beef extract with pH 11 (Sasidharan et al, 2017a) during Phases IV and V, respectively, at a pore‐water velocity of 5 m d −1 . The column effluent samples were collected using a Spectra/Chrom CF‐1 Fraction Collector (Spectrum), and the concentration of viruses was quantified using the DLA method (Sasidharan et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contamination of aquifers by virus and protozoan pathogens present a higher public health risk than bacteria due to low infectious dose and high environmental stability [48][49][50][51][52]. While viruses and protozoa are obligate intracellular parasites that require a host for metabolism, growth, and replication however, they can persist in infectious state in the groundwater under certain conditions (e.g., anoxic conditions and lower temperatures [49]).…”
Section: Pathogensmentioning
confidence: 99%